2007
DOI: 10.1111/j.1462-5822.2006.00830.x
|View full text |Cite
|
Sign up to set email alerts
|

Biological systems of the host cell involved in Agrobacterium infection

Abstract: SummaryGenetic transformation of plants by Agrobacterium, which in nature causes neoplastic growths, represents the only known case of trans-kingdom DNA transfer. Furthermore, under laboratory conditions, Agrobacterium can also transform a wide range of other eukaryotic species, from fungi to sea urchins to human cells. How can the Agrobacterium virulence machinery function in such a variety of evolutionarily distant and diverse species? The answer to this question lies in the ability of Agrobacterium to hijac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
100
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(102 citation statements)
references
References 85 publications
1
100
0
1
Order By: Relevance
“…Agrobacterium-mediated transformation of the plant cell has been extensively studied (Gelvin, 2003;Citovsky et al, 2007), whereas a comprehensive knowledge about plant host defense responses to agrobacteria is still limited. In recent years compelling evidence has demonstrated that reactive oxygen species like hydrogen peroxide (H 2 O 2 ) and hormones such as SA, JA, and ET are the primary signals inducing defense responses through recognized defense signaling pathways (Lopez et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Agrobacterium-mediated transformation of the plant cell has been extensively studied (Gelvin, 2003;Citovsky et al, 2007), whereas a comprehensive knowledge about plant host defense responses to agrobacteria is still limited. In recent years compelling evidence has demonstrated that reactive oxygen species like hydrogen peroxide (H 2 O 2 ) and hormones such as SA, JA, and ET are the primary signals inducing defense responses through recognized defense signaling pathways (Lopez et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Genes encoded by the T-DNA are expressed and subsequently alter plant hormone levels, leading to uncontrolled cell division and tumor formation. Although the elucidation of plant factors supporting the transformation process has been crucial to our understanding of this interaction (Gelvin, 2003;Citovsky et al, 2007) little is known about the timing and type of responses that plants mount against Agrobacterium and how those compare with responses elicited by other pathogens and symbionts.…”
Section: Introductionmentioning
confidence: 99%
“…The plant defense interfere at any step of A. tumefaciens-mediated transformation, starting with the attachment of bacteria to the plant cell and ending with gene expression and stable integration of T-DNA into the plant genome. 31) Recently, it has been reported that VIP1 (VirE2-interacting protein 1) is a transcription factor that is a direct target of A. tumefaciens-induced mitogen-activated protein kinase MPK3. 32) MPK3-dependent phophorylation of VIP1 is necessary for nuclear delivery of the T-DNA complex, which leads to enhanced A. tumefaciens transformation.…”
Section: Discussionmentioning
confidence: 99%
“…Development of this transformation technology represents the culmination of many decades of effort to improve tissue culture and plant genetic engineering techniques. Agrobacteriummediated transformation is based on a conjugative transfer-like process, which eventually takes the T-DNA to the host cell nucleus (Gelvin, 2000(Gelvin, , 2003a(Gelvin, , 2009Tzfira and Citovsky, 2003;Citovsky et al, 2007). After attachment of the bacterium to plant cells and induction of Agrobacterium virulence (vir) genes, a single-stranded DNA (the T-strand) is processed from the resident tumor-inducing or root-inducing plasmid and transported from the bacterium to the plant cell.…”
Section: Introductionmentioning
confidence: 99%